A Lost Illusion. Picturesque Gardens in the First Part ofthe 18th Century - Jámbor, Imre (4D Journal of Landscape Architecture and Garden Art, 2006)
The 18th century might be the last historical period when harmony seemed to be present between nature and society. We had knowledge and experience regarding the phenomenon of nature and we were willing to adapt to it with the hope of renewal and rebirth. After the late baroque style, as a conclusion of the rediscovery of nature, picturesque gardens were established which followed the rules of the age’s landscape painting. The aesthetes. the poets, the painters and naturally the landscape architects aimed to visualize the free nature and the ideal land by leaving behind the tradition of the late baroque style
Keywords: picturesque garden; 18th century